2021
DOI: 10.1051/ro/2020035
|View full text |Cite
|
Sign up to set email alerts
|

A location-allocation model for quality-based blood supply chain under IER uncertainty

Abstract: Providing blood with high quality at the lowest cost and the shortest time is main challenge of blood supply chain management. This paper presents a new model for designing a dynamic and three level blood supply chain incorporating the quality issues. The proposed model intends to locate facilities, and to determine the best strategy for blood allocation by minimizing both cost and time and maximizing the customer satisfaction based on quality of blood delivery. In order to deal with consideration of real worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It has also been observed that there are many studies devoted solely to the distribution of the platelets product. Besides, some studies follow the strategy of collecting blood products directly by apheresis (Ghatreh Samani et al , 2020; Ghatreh Samani and Hosseini-Motlagh, 2021a; Haeri et al , 2020; Hosseini-Motlagh et al , 2020a; Jemai and Sarkar, 2019; Jin et al , 2021; Larimi and Yaghoubi, 2019; Moslemi and Pasandideh, 2021; Osorio et al , 2018b). Apheresis is used to draw out only the needed components (platelets and red blood cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that there are many studies devoted solely to the distribution of the platelets product. Besides, some studies follow the strategy of collecting blood products directly by apheresis (Ghatreh Samani et al , 2020; Ghatreh Samani and Hosseini-Motlagh, 2021a; Haeri et al , 2020; Hosseini-Motlagh et al , 2020a; Jemai and Sarkar, 2019; Jin et al , 2021; Larimi and Yaghoubi, 2019; Moslemi and Pasandideh, 2021; Osorio et al , 2018b). Apheresis is used to draw out only the needed components (platelets and red blood cells).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers use some metrics to measure Pareto's front quality. These are: quality metric, divergence metric, spacing metric, mean ideal distance metric, convergence metric, diversity, hypervolume, CPU-time, lexicographic weighted Tchebycheff, multiobjective coefficient of variation and number of Pareto Blood supply chain network design solution (Behroozi et al, 2021;Eskandari-Khanghahi et al, 2018;Ghorashi et al, 2020;Khalilpourazari et al, 2020;Moslemi and Pasandideh, 2021;Mousavi et al, 2021;Shirazi et al, 2021;Zahiri et al, 2018). For converting multiobjective models to single objective models, the researchers mostly prefer the «-constraint method.…”
Section: Findings On Blood Supply Chain Network Design and Innovative...mentioning
confidence: 99%